Making sense of the college curriculum : faculty stories of change, conflict, and accommodation - Zemsky, Robert, 1940-; Wegner, Gregory R., 1950-; Duffield, Ann, 1947- (Rutgers University Press, 2018)
Over 185 faculty members from eleven colleges and universities share personal, humorous, powerful, and poignant stories about their experiences in higher education. Collectively, these accounts help to answer the question of why developing a structured and coherent undergraduate education is such a vexing challenge for colleges and universities.